Ehlers-Danlos Syndrome in Pregnancy: A Review. (December 2020) - Kang, Jungwoo; Hanif, Moghees; Mirza, Eushaa; Jaleel, Shazia
ABSTRACT: Ehlers-Danlos syndrome (EDS) is a group of connective tissue disorders that can result in a range of complications during pregnancy. Pregnant EDS patients generally have a favourable outcome, but those with vascular EDS are more likely to suffer from severe maternal complications. Early diagnosis of EDS and subtype characterization can aid in pre-pregnancy counselling, planning of antenatal care, risk assessment of obstetric and neonatal complications, and influence both obstetric and anaesthetic management of these patients. This piece aims to outline the obstetric implications of classical, hypermobile, and vascular EDS, and review the current literature regarding their optimal obstetric management.